2015
DOI: 10.1016/j.meegid.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative population genetics of two invading ticks: Evidence of the ecological mechanisms underlying tick range expansions

Abstract: Two species of ixodid tick, Ixodes affinis Neumann and Amblyomma maculatum Koch, are simultaneously expanding their ranges throughout the mid-Atlantic region of the US. Although we have some understanding of the ecology and life history of these species, the ecological mechanisms governing where and how new populations establish and persist are unclear. To assess population connectivity and ancestry, we sequenced a fragment of the 16S mitochondrial rRNA gene from a representative sample of individuals of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 86 publications
2
13
0
Order By: Relevance
“…Genetic evidence indicates that long distance dispersal must be taking place in order to facilitate gene flow between remote populations, and that geographically proximate populations of A. maculatum do not have higher levels of gene flow than distant ones (Nadolny et al, 2015). This recent study suggests that a combination of mammalian and avian hosts are likely responsible for dispersal, but that dispersal of immatures by migratory birds is necessary to facilitate the observed gene flow between far-flung populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic evidence indicates that long distance dispersal must be taking place in order to facilitate gene flow between remote populations, and that geographically proximate populations of A. maculatum do not have higher levels of gene flow than distant ones (Nadolny et al, 2015). This recent study suggests that a combination of mammalian and avian hosts are likely responsible for dispersal, but that dispersal of immatures by migratory birds is necessary to facilitate the observed gene flow between far-flung populations.…”
Section: Discussionmentioning
confidence: 99%
“…All ticks collected from flags and from hosts were identified to species using morphological characters (Clifford et al, 1961; Keirans and Durden, 1998). If morphological identification was impossible because of uncertain morphological characters or damage to the specimen, a fragment of the 16S mitochondrial rRNA gene was sequenced using previously established methods (Nadolny et al, 2015) to determine tick species. While adult A. maculatum are morphologically distinct from other U.S. ticks in the genus Amblyomma , immatures can be difficult to tell apart from other Amblyomma and Dermacentor species, especially when engorged.…”
Section: Methodsmentioning
confidence: 99%
“…Ferrari et al [ 30 ] suggested expansion of this tick along a migrating front rather than as long-standing sporadic, isolated populations. Nadolny et al [ 31 ] used genetic analysis to track the ancestry of newly established populations. Their findings showed diverse haplotypes but there was no significant relationship to geographic distribution and little or no apparent connectivity between the many different localities.…”
Section: Selected North American Ticks and Range Expansionmentioning
confidence: 99%
“…The recent application of molecular techniques to parasitic organisms has provided insightful information on their biology and ecology, which has been useful to measure parasite population structuring and to approach the factors associated with divergence, such as spatial isolation and host type. However, understanding the relative importance of these factors in structuring populations can be particularly challenging when parasites have broad distributions and use several host species to complete the life cycle (Dupraz et al, 2016;Mazé-Guilmo et al, 2016;Nadolny et al, 2015). This is frequently the case for ticks, where two or more phylogenetically distant hosts may be used for blood feeding in immature and adult life stages.…”
Section: Introductionmentioning
confidence: 99%